Prenatal Diagnosis of Pentalogy of Cantrell with Increased Nuchal Translucency: Case Report - Arıkan, Deniz Cemgil; Yancar, Semih; Güçer, Fethi; Zencir, Ender; Beyazıt, Hakan (Gynecology Obstetrics & Reproductive Medicine, 2011)
Pentalogy of Cantrell is a rare sporadic syndrome with unknown etiology. We aimed to present a prenatally diagnosed case of pentalogy of Cantrell associated with increased nuchal translucency (NT). A twenty-two year old G2P0A1 pregnant woman was admitted to our clinic for routine prenatal ultrasonographic scanning at 14th weeks of gestation. Ultrasound scan revealed a NT of 7.9 mm and a large omphalocele containing the liver, bowel, and heart with ventricular septal defect. After taking the written informed consent form the parents the pregnancy was terminated. Postmortem examination confirmed the ultrasound findings and chromosome analysis revealed a normal karyotype. Increased NT measurement in first trimester of pregnancy may also bring the fetus to early attention for pentology of Cantrell if an omphalocele associates with this condition.